Financial Stability and the Fed: Evidence from Congressional Hearings - Arina Wischnewsky; David-Jan Jansen; Matthias Neuenkirch (ZBW - Leibniz Information Centre for Economics, 2020)
This paper retraces how financial stability considerations interacted with U.S. monetary policy before and during the Great Recession. Using text-mining techniques, we construct indicators for financial stability sentiment expressed during testimonies of four Federal Reserve Chairs at Congressional hearings. Including these text-based measures adds explanatory power to Taylor-rule models. In particular, negative financial stability sentiment coincided with a more accommodative monetary policy stance than implied by standard Taylorrule factors, even in the decades before the Great Recession. These findings are consistent with a preference for monetary policy reacting to financial instability rather than acting pre-emptively to a perceived build-up of risks.
Keywords: E52; E58; N12; 330; monetary policy; financial stability; Taylor rule; text mining